Effect of CEO Characteristics Toward Tax Aggressiveness: Overview of Indonesia Family Firms - Rachmawati Meita Oktaviani, Kukrit Wicaksono, (Jurnal Ekonomi, 2021)
This study aims to examine the relationship between CEO tenure and risk preferences) toward tax aggressiveness of Indonesia family firms. Tax Aggressiveness in this study became the dependent variable, meanwhile the independent variables consisted of CEO tenure and CEO risk preferences. Profitability is also included in the study as a control variable. The family companies listed on IDX during 2016 to 2019 period are used as sample of this research. The data collection method used purposive sampling. The total sample that can be collected through this method is 70 samples with 280 observations. This study uses a panel data regression analysis model with a random effect model estimation model. The results obtained through the regression test indicate that the tenure and risk preferences of the CEO have an effect toward tax aggressiveness.